2020
DOI: 10.1111/dth.14677
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin in acne treatment during the coronavirus disease 2019 ( COVID ‐19): A retrospective analysis of adherence to therapy and side effects

Abstract: genesis of COVID-19 infection, isotretinoin should be utilized at low dose with proper care of the nasal mucosa.Isotretinoin is an oral retinoid approved for the management of severe cases of acne vulgaris, and recently utilized for mild to moderate acne. 2 COVID-19, is a respiratory disease caused by the SARS-CoV-2 virus and it was stated a pandemic on 11 March 2020. Advanced age

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The other one was on a daily dose of 40 mg of ISO for 4 months, presented with mild fever and headache. 5 Donnarumma et al 4 noted four of 34 patients on ISO reported cough and rhinorrhea; of them, only two patients reported 2-day elevation of body temperature not over 37.5. However, none had been diagnosed for COVID-19.…”
Section: Could Isotretinoin Be a Protective Agent Against Covid-19?: A Dermatologist Perspectivementioning
confidence: 99%
“…The other one was on a daily dose of 40 mg of ISO for 4 months, presented with mild fever and headache. 5 Donnarumma et al 4 noted four of 34 patients on ISO reported cough and rhinorrhea; of them, only two patients reported 2-day elevation of body temperature not over 37.5. However, none had been diagnosed for COVID-19.…”
Section: Could Isotretinoin Be a Protective Agent Against Covid-19?: A Dermatologist Perspectivementioning
confidence: 99%
“…Isotretinoin, an oral medication primarily used to treat severe acne, is thought to increase coronavirus invasion of the nasal mucosa due to its drying effect on the mucous membranes. 17 However, there is mounting evidence that supports the use of this drug. It protects against COVID-19 by downregulation of ACE2 receptors, reducing coronavirus entry into susceptible cells.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Despite this, and despite the lower risk for COVID-19 in the customary isotretinoin adolescent and young adult age range, an Italian study reported that 14.7% of patients (5/34) prematurely interrupted isotretinoin therapy during lockdown because of fear of COVID-19 infection. 6 Data also suggest that college towns (akin to where I practice, rife with isotretinoin-eligible patients) reflected higher COVID-19 infection and death rates, likely due to dense cohabitation and intermittent migration of students and staff to and from campuses and within their communities. 7 Approximately 30% of my patients on isotretinoin in the last 18 months reported having COVID-19 at some point during the pandemic, though no data exist to guide us on whether isotretinoin should be discontinued in this scenario; my patients typically continued the drug unless their primary health care team discouraged it, and in those cases, all of them resumed it after COVID-19 symptomatology resolved.…”
Section: Impact Of Covid-19 On Isotretinoin Usementioning
confidence: 93%